Preoperative diagnosis of gallbladder torsion by magnetic resonance cholangiopancreatography: A case report. Issue 2 (23rd February 2022) - Miyata, Takashi; San‐nomiya, Yuta; Nagayama, Taigo; Kin, Ryosuke; Nishiki, Hisashi; Hashimoto, Akifumi; Fujii, Yoritaka; Miura, Seiko; Kaida, Daisuke; Tomita, Yasuto; Nakamura, Naohiko; Miyashita, Tomoharu; et al.
Abstract: Gallbladder torsion is a rare and potentially fatal condition presenting with acute abdominal pain. Gallbladder torsion requires early diagnosis and treatment; however, preoperative diagnosis is difficult. In the present case, magnetic resonance cholangiopancreatography provided definitive imaging findings and was very useful in making the preoperative diagnosis. Abstract : Gallbladder torsion is a rare but potentially fatal condition that can be difficult to diagnose preoperatively. Magnetic resonance cholangiopancreatography has numerous advantages and can be very useful in making the preoperative diagnosis.